Association of capsular types with carbapenem resistance, disease severity, and mortality in Acinetobacter baumannii - Yu-Chia Hsieh; Shi-Heng Wang; Yi-Yin Chen; Tzu-Lung Lin; Shian-Sen Shie; Ching-Tai Huang; Chen-Hsiang Lee; Yi-Ching Chen; Tran Lam Tu Quyen; Yi-Jiun Pan (Emerging Microbes and Infections)
Acinetobacter baumannii emerged as one of the most important pathogens that causes nosocomial infections due to its increased multidrug resistance. Identifying capsular epidemiology in A. baumannii can aid in the development of effective treatments and preventive measures against this emerging pathogen. Here we established a wzc-based method, and combined it with wzy-PCR to determine capsular types of A. baumannii causing nosocomial bacteraemia collected at two medical centres in Taiwan from 2015 to 2017. Among the 237 patients with A. baumannii bacteraemia, 98 (41.4%) isolates were resistant to carbapenems. Four prevalent capsular types (KL2, KL10, KL22, and KL52) accounted for 84.7% of carbapenem-resistant A. baumannii (CRAB) and 12.2% of non-CRAB. The rate of pneumonia, intensive care unit admission, APACHE II score, and Pitt bacteraemia score were higher in patients with KL2/10/22/52 infection than in those with non-KL2/10/22/52 infection. Patients with KL2/10/22/52 infection and patients with CRAB infection have a higher cumulative incidence of attributable and all-cause in-hospital 30-day mortality. On multivariate analysis, appropriate empirical antimicrobial therapy within 24 h was associated with a lower risk of 30-day attributable mortality in the KL2/10/22/52 isolates (odds ratio = 0.19, 95% CI: 0.06–0.66, p = 0.008) but not in non-KL2/10/22/52 isolates. Early recognition of carbapenem resistance-associated capsular types may help clinicians to promptly implement appropriate antimicrobial therapy for improving the outcomes in patients with CRAB bacteraemia.